Mechanisms for cholesterol homeostasis in rat jejunal mucosa: effects of cholesterol, sitosterol, and lovastatin - Lien B. Nguyen; Sarah Shefer; Gerald Salen; G.S. Tint; Frank Ruiz; John Bullock (Journal of Lipid Research, 2001)
The effects of feeding cholesterol, sitosterol, and lovastatin on cholesterol absorption, biosynthesis, esterification, and LDL receptor function were examined in the rat jejunal mucosa. Cholesterol absorption was measured by the dual-isotope plasma ratio method; the rate-limiting enzyme of cholesterol biosynthesis, 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, was measured as total and expressed enzyme activities (in the absence and presence of a phosphatase inhibitor, NaF, respectively); mucosal total and esterified cholesterol concentrations were determined by gas-liquid chromatography; LDL receptor function was assayed as receptor-mediated binding of 125I-labeled LDL to mucosal membranes. Feeding 2% sitosterol or 0.04% lovastatin for 1 week significantly (P < 0.01) decreased the amounts of cholesterol absorbed per day (−85% and −63%, respectively). In contrast, feeding 2% cholesterol for 1 week increased the amounts of absorbed cholesterol 27-fold, even though the percent absorption significantly decreased. With all three treatments, there was a coordinate regulation of total HMG-CoA reductase activity and receptor-mediated LDL binding. Cholesterol feeding downregulated both total jejunal HMG-CoA reductase activity (P < 0.05) and receptor-mediated LDL binding (P < 0.01), whereas lovastatin- and sitosterol-supplemented diets significantly upregulated both of these parameters. In the control, cholesterol-fed, and sitosterol-fed animals, about half of the total jejunal HMG-CoA reductase activity was expressed (in functional dephosphorylated form). However, in the lovastatin-treated rats with 4-fold stimulation of HMG-CoA reductase, only 23% of the total enzyme activity was expressed. Changes in total HMG-CoA reductase activity and receptor-mediated LDL binding in all tested groups occurred with no change in total concentrations of mucosal cholesterol, and only cholesterol-fed animals had increased mucosal esterified cholesterol concentrations. Thus, in response to various fluxes of dietary or newly formed cholesterol, HMG-CoA reductase and receptor-mediated LDL binding are coordinately regulated to maintain constant cellular cholesterol concentrations in the jejunum. —Nguyen, L. B., S. Shefer, G. Salen, G. S. Tint, F. Ruiz, and J. Bullock. Mechanisms for cholesterol homeostasis in rat jejunal mucosa: effects of cholesterol, sitosterol, and lovastatin.